2014
DOI: 10.3349/ymj.2014.55.1.264
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Outcomes in Children with Epidermolysis Bullosa: The Experiences of Two Centers in Korea

Abstract: PurposeEpidermolysis bullosa (EB) is associated with variable risks of extracutaneous manifestations and death. Currently, there is limited information on the clinical course and prognosis of EB in Korea. This study analyzed the nutritional outcomes, clinical morbidity, and mortality of children with EB.Materials and MethodsThirty patients, admitted to Severance Hospital and Gangnam Severance Hospital, from January 2001 to December 2011, were retrospectively enrolled. All patients were diagnosed with EB classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Nutritional compromise is regarded as the main factor contributing to underweight in RDEB . We found that hypalbuminaemia, a feature previously reported in EB, correlated significantly with low weight in RDEB. As average protein and energy intake are well below general recommendations in children with RDEB while protein turnover is increased because of constant wound healing, the body is driven into an autocatabolic state .…”
Section: Discussionsupporting
confidence: 74%
“…Nutritional compromise is regarded as the main factor contributing to underweight in RDEB . We found that hypalbuminaemia, a feature previously reported in EB, correlated significantly with low weight in RDEB. As average protein and energy intake are well below general recommendations in children with RDEB while protein turnover is increased because of constant wound healing, the body is driven into an autocatabolic state .…”
Section: Discussionsupporting
confidence: 74%
“…The mutation is usually a dominant negative missense mutation most frequently in the keratin 14 gene (Coulombe and Lee 2012). The result is a separation in the skin at the dermo-epidermal junction that can lead to infection and dehydration (Kim et al 2014; Garcia Perez 1999). 4) Keratinocytes in which all cytokeratins were deleted had a 60% increase in deformability compared to normal cells (Ramms et al 2013; Seltmann et al 2013).…”
Section: Epidermis Organization and Regulation Of Homeostasismentioning
confidence: 99%
“…Malnutrition is highly prevalent in EB, with 56% of patients below the 3 rd centile for weight, with a higher incidence in JEB and RDEB [ 28 ], thus the importance of establishing a nutrition-based approach to the disease [ 29 ]. Malnutrition can indeed interfere with the entire hormonal system and, accordingly, the hypothalamo-pituitary-gonadal axis.…”
Section: Discussionmentioning
confidence: 99%